Xun Pang and Chong Chen, “The Hirschman Effect of China’s Bilateral Cross-Currency SWAP Agreements” (World Economy and Politics (in Chinese), 2020)
Bilateral cross-currency SWAP agreements (BSAs) were rejuvenated during the GFC by the Federal Reserve of the United States to provide liquidity to selected governments in dire financial straits. After the crisis, BSAs rapidly and widely spread around the globe and become a major component of the global financial safety net. Interestingly, it is not the United States but China which occupies the center of the global BSA network. China has signed BSAs with a diverse pool of states since 2009, and has far more partners than any other countries. While existing studies mainly focus on the motivations driving China and its partner states to enter BSAs, this paper is intended to evaluate foreign policy consequences of China’s BSAs. Asymmetric interdependence and asymmetric information, as two key features of the economic relationship between China and its partner states in BSAs, are expected to make other countries be more supportive to China’s position in global affairs, leading to a convergence of their foreign policy preferences. This is the classic “Hirschman effect”. To empirically identify the “Hirschman effect”, we use measures of states’ foreign policy ideal points based on votes in the United States General Assembly. We apply a quantitative analysis to estimate the average effect and conduct a case study to trace and explain the development of the effect over time. In the large-N study, we draw data on 191 countries between 2009 and 2018 and specify a multilevel model with varying intercepts to control for unobserved heterogeneity in the dimension of time and space. Empirical evidence suggests that BSAs significantly drive the foreign policy preferences of China and other states to converge. Then we focus on Argentina as an in-depth case study. Different from conventional case studies, we conduct a “quantitative case study” and apply the Synthetic Control Method to estimate and quantify the causal effect of signing a BSA with China in 2009 on the distance between foreign policy ideal points of Argentina and China. The case study confirms the presence of the “Hirschman effect” suggested by theory and found in the regression analysis. It further reveals several suggestive but interesting points, including 1) activating SWAP lines may strengthen the effect, whereas the effect may be weakened by the provision of emergency liquidity assistance from the US or the IMF; 2) BSAs with China may impact on left-wing governments more strongly than right-wing governments; and 3) the Chinese government may strengthen the effect by changing the size of the committed SWAP line.